2007
DOI: 10.1007/s12035-007-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Synaptic Transmission at Ribbon Synapses of Rods and Cones

Abstract: The ribbon synapse is a specialized structure that allows photoreceptors to sustain the continuous release of vesicles for hours upon hours and years upon years but also respond rapidly to momentary changes in illumination. Light responses of cones are faster than those of rods and, mirroring this difference, synaptic transmission from cones is also faster than transmission from rods. This review evaluates the various factors that regulate synaptic kinetics and contribute to kinetic differences between rod and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 227 publications
(386 reference statements)
2
80
0
1
Order By: Relevance
“…2005; Thoreson, 2007). For example, a ribbon in a dissociated bipolar neuron, when strongly depolarized, can fuse ϳ500 vesicles s Ϫ1 (von Gersdorff et al, 1996), and similar rates were found in auditory hair cells (Parsons et al 1994).…”
Section: Discussionmentioning
confidence: 82%
“…2005; Thoreson, 2007). For example, a ribbon in a dissociated bipolar neuron, when strongly depolarized, can fuse ϳ500 vesicles s Ϫ1 (von Gersdorff et al, 1996), and similar rates were found in auditory hair cells (Parsons et al 1994).…”
Section: Discussionmentioning
confidence: 82%
“…Glutamate release in these synapses is controlled via graded and sustained changes in membrane potential that are maintained throughout the duration of a light stimulus (1,2). In recent years, it became clear that Cav1.4 L-type Ca 2ϩ channels are the main channel subtype converting these analog input signals into corresponding permanent glutamate release (1,(3)(4)(5). In support of this mechanism, mutations in the Cav1.4 gene have been identified in patients suffering from congenital stationary night blindness type 2 and X-linked cone rod dystrophy (6 -8).…”
mentioning
confidence: 99%
“…Cones have faster light response kinetics than rods (Hestrin and Korenbrot, 1990;Thoreson, 2007), which allows them to have higher FFFs. Cones are, however, less sensitive to light, and their responses decline rapidly with decreasing light intensity Wolf, 1939, 1941;Hestrin and Korenbrot, 1990;Meneghini and Hamasaki, 1967).…”
Section: Characterising the Photoreceptor Typementioning
confidence: 99%
“…This suggests that the response kinetics of the photoreceptor within Mordacia spp. are slow (Thoreson, 2007) and may be rod like.…”
Section: Characterising the Photoreceptor Typementioning
confidence: 99%
See 1 more Smart Citation